The Role of BMT Amanah in Empowering Micro, Small, and Medium Enterprises (UMKM) in Bekasi in the Perspective of Islamic Law - Syaeful Anwar; Irvan Iswandi; Ahmad Asrof Fitri (JOURNAL of LEGAL RESEARCH, 2022)
BMT Amanah Sariah provides savings, financing, payment, deposits services, focusing on serving MSMEs using easy procedures and mechanisms, and being in the midst of small or rural communities. BMT as an extension of Islamic Banks can channel the financing that has been entrusted to it. The research objective was to determine the role of financial institutions in empowering small micro enterprises. This type of research is qualitative research. The data obtained through observation, interviews, and documentation. The results of the study show that BMT Amanah Syariah Bekasi has good potential and role in supporting the empowerment of MSMEs that provide financing services to the community. In this case BMT Amanah Syariah Bekasi has also played a very important role in helping small communities who want to open a business, starting from starting a customer's business so that the customer's business develops. The roles of BMT Amanah Syariah Bekasi are: helping the capital of its members; Developing the entrepreneurial spirit of its members; Reducing usury practices; Improving the welfare of small communities; Improvement of human resources.